2021
DOI: 10.16926/par.2021.09.21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of healthy behavior in Ukrainian and Polish students of physical education

Abstract: Introduction: This study aimed to examine the healthy behaviors in undergraduate students of Physical Education (PE) from Ukraine and Poland in comparison to the control sample of students of other faculties. Material and methods: The group of 564 university students (67% of males), ranging in age from 18 to 41 years (M = 22.05, SD = 2.49), was surveyed using a written form of the Health Behavior Inventory (HBI). The HBI includes the following four subscales: healthy habits, nutrition (HHN), preventive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In accordance with previous studies, 20 , 57 women showed higher scores than men in HD (with medium strength) and the total scores of HBI and PB (but with a small effect size). Dispositional optimism differed between genders, with higher levels in men than in women, but the effect size was small.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies, 20 , 57 women showed higher scores than men in HD (with medium strength) and the total scores of HBI and PB (but with a small effect size). Dispositional optimism differed between genders, with higher levels in men than in women, but the effect size was small.…”
Section: Discussionsupporting
confidence: 92%
“…Total scores (sum of all five items) ranged between 5 and 35, with higher scores suggesting greater life satisfaction. The ranges of scores may be interpreted as Extremely dissatisfied (5-9), Dissatisfied (10)(11)(12)(13)(14), Slightly dissatisfied (15)(16)(17)(18)(19), Neutral (20), Slightly satisfied (21)(22)(23)(24)(25), Satisfied (26)(27)(28)(29)(30), and Extremely satisfied (31)(32)(33)(34)(35). The scale shows good convergent and discriminant validity with other emotional well-being scales.…”
Section: Measures Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that university students do not exhibit satisfactory health-oriented behaviors in terms of their physical activity, diet, alcohol and drug use, preventive practices, mental health, stress, and social relationships. However, female university students performed higher in health-related behavior than men [25][26][27]. A recent study examined the health-related behaviors of university students from Poland, Croatia, Turkey, Lebanon, Spain, Romania, and Italy [28].…”
Section: Healthy Lifestyle Among University Studentsmentioning
confidence: 99%
“…Previous studies indicated that university students demonstrate a relatively low level of healthy behavior, which is related to lack of the parents' control, lack of enough time, low health literacy, and frequent social gatherings, which is related to excessive substance use and less sleep time [25][26][27][28]. Cena et al [28] suggested greater emphasis needs to be placed on improving the lifestyle of those university students who will be future healthcare workers.…”
Section: Orthorexia Fear Of Covid-19 and Pa Among University Studentsmentioning
confidence: 99%